1997
DOI: 10.1111/j.1744-9987.1997.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis for Prevention of Recurrent Focal Segmental Glomerulosclerosis of Kidney Allograft in Adult Recipients

Abstract: Nephrotic syndrome due to focal segmental glomerulosclerosis (FGS) frequently recurs even after renal transplantation and may cause renal allograft failure. From January 1983 though April 1995, 11 adult recipients with primary FGS received 11 kidney transplants at our institution, and 3 of them were treated with pretransplant plasma exchange (PE). Other patients did not receive any preoperative PE, and 4 patients lost their grafts due to recurrent FGS (50%). PE was completed 3 times before the transplantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…Iguchi et al [ 31 ] reported that the beneficial effect of pretreatment by plasma exchange was suggested. The possibility of decreasing or absorbing the potent pathogenic permeability factor might be expected in both LDL apheresis and plasma exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Iguchi et al [ 31 ] reported that the beneficial effect of pretreatment by plasma exchange was suggested. The possibility of decreasing or absorbing the potent pathogenic permeability factor might be expected in both LDL apheresis and plasma exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Even with widespread application of plasmapheresis for recurrent FSGS, relapse rates remain high, and patients may become plasmapheresis dependent (1, 2). In the case of preemptive plasmapheresis, some reports have indicated trends toward reductions in recurrence rates and a resulting improvement in graft survival benefit among high‐risk patients (8, 9). According to a literature review (Tables 3 and 4), preemptive plasmapheresis seemed to provide better outcomes for remission of FSGS when conducted along with use of rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent FSGS immediately after renal transplantation is attributed to circulating permeability factor (5). Plasmapheresis is thus used as the initial therapy for recurrent FSGS (6, 7) and also as preemptive therapy to prevent further recurrence (8, 9). Even with more widespread application of plasmapheresis, relapse rates remain high and frequently lead to graft loss (1, 2).…”
mentioning
confidence: 99%
“…Iguchi et al also tried prophylactic plasmapheresis (3 sessions) before transplantation in three patients, only one of whom had recurrence of proteinuria compared to four out of eight not receiving plasmapheresis (15). Two of the patients who had recurrence of FSGS had further plasmapheresis with one showing relative remission and stable renal function, while the other developing graft failure.…”
Section: Prophylactic Plasmapheresismentioning
confidence: 99%